Thoracic Outlet Syndrome: Single Center Experience on Robotic Assisted First Rib Resection and Literature Review - Gkikas, Andreas; Lampridis, Savvas; Patrini, Davide; Kestenholz, Peter B.; Azenha, Luis Filipe; Kocher, Gregor Jan; Scarci, Marco; Minervini, Fabrizio (Frontiers in Surgery, 2022)
Background Thoracic outlet syndrome (TOS) is a pathological condition caused by a narrowing between the clavicle and first rib leading to a compression of the neurovascular bundle to the upper extremity. The incidence of TOS is probably nowadays underestimated because the diagnosis could be very challenging without a thorough clinical examination along with appropriate clinical testing. Beside traditional supra-, infraclavicular or transaxillary approaches, the robotic assisted first rib resection has been gaining importance in the last few years. Methods We conducted a retrospective cohort analysis of all patients who underwent robotic assisted first rib resection due to TOS at Lucerne Cantonal Hospital and then we performed a narrative review of the English literature using PubMed, Cochrane Database of Systematic Reviews and Scopus Results Between June 2020 and November 2021, eleven robotic assisted first rib resections were performed due to TOS at Lucerne Cantonal Hospital. Median length of stay was 2 days (Standard Deviation: +/- 0.67 days). Median surgery time was 180 minutes (Standard Deviation: +/- 36.5). No intra-operative complications were reported. Conclusions Robotic assisted first rib resection could represent a safe and feasible option in expert hands for the treatment of thoracic outlet syndrome.